A Community-Based Environmental Empowerment Model Through Social Movements and Local Institutions: Strate-gies for Strengthening and Implementation - Agustrisno Agustrisno; Zulkifli Lubis; Fikarwin Zuska; Farid Aulia; Nita Savitri (INFOKUM, 2025)
Environmental management and village cleanliness through social movements in community empowerment efforts in Sei Nagalawan Village, Perbaungan District, Serdang Bedagai Regency, are still constrained by various factors. These include: the limited capacity of the village community to reduce the rapidly increasing volume of waste, the low level of community knowledge regarding waste management and household yard cleanliness, and weak partnerships in community-based waste management initiatives. This situation needs to be addressed through community service programs. The activities are designed to empower the PKK (Family Welfare Movement) Women’s Group, village Posyandu (Integrated Health Post) cadres, and the broader community by providing outreach and awareness-raising on the importance of maintaining a clean, waste-free environment through social movements. The objectives of this independent community service program are to: (1) contribute to reducing the alarming rate of waste generation, (2) increase the knowledge of PKK members and Posyandu cadres on waste management, and (3) strengthen local institutions as a means of fostering community-based social movements for waste management. The methods used in this program include: socialization and training on environmental management with a focus on preventing yard waste, and a participatory approach to social movements that integrates the role of local institutions. The results of this community service initiative demonstrate increased community motivation to manage waste and maintain clean household yards through social movement-based approaches.